Penerapan Sistem Full Day School dalam Kurikulum Merdeka di SD Nasima Semarang - Setyawati, Della; Hanik, Elya Umi; Nuryanti, Meila Dwi; Putri, Laisya Syifana Hariyanto Syifana (Lembaga Yasin AlSys, 2025)
Full day school is a school process throughout the day or a teaching and learning process that is implemented from morning to evening. The implementation of the full day school system is an alternative for parents of students at SD Nasima Semarang who are busy working, with lots of learning time students are able to take part in more in-depth learning of the material taught by the teacher. This research aims to determine the implementation of the full day school system as an effort to improve the quality of learning at Nasima Elementary School, Semarang. The approach used is a qualitative descriptive approach. Field study data analysis techniques are carried out using observation and documentation. Observations are used as data reinforcement. Documentation is used as supporting data. The superior programs implemented include Koran reading, computers, English and Arabic. Furthermore, there are extracurricular activities including: Swimming, Badminton, Origami, Science Club, Drawing, Taekwondo, Pre-Olympics, Robotics, Dancing, Futsal, Coding, Robotics, Pencak Silat, Videography, Olympics, Tambourine, Band, etc. Which can be used as a means of developing students' talents and interests.